PELAKSANAAN DIVERSI TERHADAP ANAK SEBAGAI PELAKU TINDAK PIDANA DI PENGADILAN NEGERI SIDOARJO - Maulani, Zihan; Kartika, Adhitya Widya (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
Children are the younger generation as the successor of the nation’s ideals and also play a role as national development in the future, so that guidance and protection are needed to ensure protection from all things that can damage children’s future. The development of science and technology makes criminal acts committed by children increasingly rampant. The implementation of diversion is motivated by the desire to avoid negative effects on the psychological and mental health of children due to their involvement with the criminal justice system. However, in practice the implementation of diversion often fails, especially when it reaches the District Court level, this causes children to have to deal directly with the formal criminal justice process. Furthermore, juvenile criminal justice can have a negative impact in the form of evil stigmatization of children as perpetrators of criminal acts which can increase deviant behavior and form criminal characters so that it is difficult for children to return to their natural environment. This study uses an empirical juridical method using empirical facts taken directly verbally, namely interviews. The results of this study are that cases of criminal acts committed by children in the Sidoarjo District Court experience more failure than success, this makes children as perpetrators of criminal acts have to undergo further criminal justice processes. There are factors that support and hinder the implementation of diversion at the Sidoarjo District Court so that it often fails. Against this condition, the Sidoarjo District Court seeks to overcome the inhibiting factors for the implementation of diversion by increasing the quality and quantity of law enforcers within the Sidoarjo District Court, increasing cooperation with related law enforcement agencies to resolve disputes between parties, and updating the facilities and infrastructure for special rooms to implement examination of children as perpetrators of criminal acts